Development and validation of a total quality management model for Uganda's local governments - Ibrahim Abaasi Musenze; Mayende Sifuna Thomas (Cogent Business & Management, 2020)
The objectives of this study were to provide reliable and valid constructs of TQM and a measurement model in the context of Uganda's local governments (LGs) for evaluation of TQM implementation process. The paper used survey-based data from Uganda's LGs. Data were analysed through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) using Analysis of moment structure (AMOS) version 20 software. Through EFA and CFA procedures, the findings show support for reliability and validity of the new TQM scale. Managerially, the instrument presented provides Uganda's LGs with an understanding of TQM implementation to inform quality delivery. Practitioners therein, will also be able to use this instrument to evaluate their TQM implementation so as to target improvement areas. The study contributes to theory through development and validation of an original parsimonious TQM scale for the LGs that can be used to improve quality delivery.
Keywords: 650; total quality management; exploratory factor analysis; confirmatory factor analysis; instrument validation